Pengembangan Sistem Kontrol Akses Pintu Berbasis Iot Menggunakan Mikrokontroler Esp32 Dan Firebase Auth - Isarianto, Isarianto; Setiyaningrum, Widiya (Universitas Pelita Bangsa, 2024)
The advancement of Internet of Things (IoT) technology has enhanced security systems, especially in automated door access management. This research designs and develops an IoT-based door access control system using an ESP32 microcontroller, RFID for user authentication, and integration of Firebase Authentication and the MQTT protocol to ensure secure and real-time communication. The system was developed using the prototyping method, including requirements analysis, system design, development, and evaluation. The frontend is implemented as a Progressive Web App (PWA) using React.js for responsive access on mobile and desktop devices, while the backend uses Express.js integrated with Firebase and an MQTT broker. Testing results show that the system enables real-time door access control with improved security and efficiency. The use of Google Authentication and HTTP-only cookies enhances protection against unauthorized access, and the access log feature supports user activity monitoring. Overall, the system provides a modern, secure, and integrated door access solution suitable for various environments